A Single-Center, Retrospective, Real-World, Observational Clinical Study to Evaluate the Safety and Efficacy of Abiraterone (Abiratred) in Patients with Metastatic Prostate Cancer - Danchaivijitr, Pongwut; Archwamety, Anita; Wongkraisri, Concord (South Asian Journal of Cancer, 2025)
Prostate cancer ranks as the eighth leading cause of cancer-related mortality in Thailand, exhibiting an average annual percent increase in incidence rates of 2.7%. Abiraterone acetate, an active prodrug of abiraterone, exhibits potent inhibitory activity against the enzyme CYP17A1, a crucial component in the androgenic biosynthetic cascade. This study was designed to evaluate the safety and efficacy of generic abiraterone (Abiratred) in treating metastatic prostate cancer within a real-world, retrospective observational context.Thirty-five patients diagnosed with metastatic prostate cancer who underwent abiraterone treatment at Siriraj Hospital in Thailand were enrolled in the study. Data encompassing demographics, medical history, general examination, vital signs, comorbidities, health status, and prostate cancer-related characteristics were collected. The primary outcome measure was the prostate-specific antigen (PSA) response rate (defined as a ≥ 50% decrease in PSA levels from baseline), and secondary outcomes encompassed assessing PSA progression-free survival (PFS), disease control rate (DCR), and evaluating safety.Among the 35 patients, 23 (65.7%) exhibited a PSA response. The median PSA PFS at 6 months was 65.6% (21 out of 35 patients). The DCR was determined to be 71.4% (25 out of 35 patients), with 19 (54.3%) patients experiencing stable disease and 6 (17.1%) patients showing a partial response. Adverse events were observed in 5 (14.3%) patients, but there were no deaths related to abiraterone.This real-world study provides evidence that generic abiraterone (Abiratred) is both well-tolerated and effective for patients with advanced or metastatic prostate cancer, making it a promising option in real-world clinical settings.
Keywords: abiraterone; androgen deprivation therapy; prostate cancer; prostate-specific antigen; real-world study